La comunicazione di marketing nelle piccole imprese: alcune evidenze empiriche - Pencarelli, Tonino; Cioppi, Marco (Piccola Impresa / Small Business, 2009)
In this paper we discuss about marketing communication activities in a group ofItalian Small Enterprises (SEs) studied with a qualitative approach of research . It resultsthat traditional marketing mainstream is not suitable for SEs and that communication ofmarketing activities is a crucial activity for survival and development of firms. The mixcommunication of SEs is very narrow: they mainly use web sites, brochures and catalogues,trade fairs, direct mailings. Face to face and networking communications of the entrepreneursand sales people are extremely important as they realize and put in actions in according torelational marketing principles. The challenge for Italian SEs is to increase the marketingcommunication capabilities and to introduce qualified human resources, above all youngprofessional people exploiting networks with universities and post graduate businessschools and to improve the ability to show and to communicate the value proposition tothe market.